DEVELOPMENT OF AN EARLY-MATURING VARIETY OF CITRUS GRAPEFRUIT (CITRUS PARADISI M) - Sirojiddin Turdiqulovich Jurayev; Maftuna Halimjonovna Maxmudjonova; Gulchehra Abdikarimovna Narmatova (Modern American Journals, 2025)
A new variety of citrus grapefruit was developed by grafting the local pomelo variety "Zaynutdin" onto the lemon variety F-2 Yubileiny under greenhouse conditions, cultivating the plant in a dwarf and compact form. By cross-pollinating maternal and paternal flowers, a new variety named O‘zbegim was created and introduced into production.
Keywords: Pure line, selection, hybrid, crossbreeding, disease, productivity, cold resistance, young, newly developed, branch.